A cross‐cultural convergent parallel mixed methods study of what makes a cancer‐related symptom or functional health problem clinically important. Issue 2 (21st September 2017) - Giesinger, Johannes M.; Aaronson, Neil K.; Arraras, Juan I.; Efficace, Fabio; Groenvold, Mogens; Kieffer, Jacobien M.; Loth, Fanny L.; Petersen, Morten Aa.; Ramage, John; Tomaszewski, Krzysztof A.; Young, Teresa; Holzner, Bernhard; et al.
Abstract: Objective: In this study, we investigated what makes a symptom or functional impairment clinically important, that is, relevant for a patient to discuss with a health care professional (HCP). This is the first part of a European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Group project focusing on the development of thresholds for clinical importance for the EORTC QLQ‐C30 questionnaire and its corresponding computer‐adaptive version. Methods: We conducted interviews with cancer patients and HCPs in 6 European countries. Participants were asked to name aspects of a symptom or problem that make it clinically important and to provide importance ratings for a predefined set of aspects (eg, need for help and limitations of daily functioning). Results: We conducted interviews with 83 cancer patients (mean age, 60.3 y; 50.6% men) and 67 HCPs. Participants related clinical importance to limitations of everyday life (patients, 65.1%; HCPs, 77.6%), the emotional impact of a symptom/problem (patients, 53.0%; HCPs, 64.2%), and duration/frequency (patients, 51.8%; HCPs, 49.3%). In the patient sample, importance ratings were highest for worries by partner or family, limitations in everyday life, and need for help from the medical staff. Health care professionals rated limitations in everyday life and need for help from the medical staff to be most important. Conclusions: Limitations in everyday life, need for (medical) help, and emotional impact on the patient or family/partner were found to be relevant aspects of clinical importance. Based on these findings, we will define anchor items for the development of thresholds for clinical importance for the EORTC measures in a Europe‐wide field study.